An overview of the chemical modifications of chitosan and their advantages. Issue 4 (23rd October 2018) - Madera-Santana, Tomás Jesús; Herrera-Méndez, Carlos Hernán; Rodríguez-Núñez, Jesús Rubén
Abstract : The use of chitosan, a natural polymer, has recently increased due to its antimicrobial and antifungal character, null toxicity, biocompatibility and ability to form biofilms and hydrogels. The areas of application and research include biomedical, pharmaceutical, biomaterials, water treatment and haircare and skincare products. However, the applications of chitosan are limited due to the difficulty associated with modification of its structure and its poor solubility in water. Among the main chemical modifications for functionalising the chitosan structure are the N-substitution, O-substitution (with or without protecting the reactive sites of the chitosan) and cross-linking with other compounds; these chemical modifications allow improvement of its chemical and physical properties. In relation to the current importance of the use of chitosan with chemical modification, the present review attempts to explain in a simple way the main chemical reactions carried out with chitosan and its wide range of applications, and provides a future perspective.